Using AI and Machine Learning Efficiently to Decide on Voyage Fixture of Tanker Ships to Increase Turnarounds and Profitability - Balaji, Sathya Narayan (Digital Repository of Theses - SSBM Geneva, 2025)
This research investigates how the use of Artificial intelligence (AI) & Machine learning (ML) concepts can forecast turnaround times at shipping ports, with a focus on the tanker shipping industry. The study intends to improve vessel turnaround efficiency by examining a variety of market conditions, which will ultimately result in higher profitability. It examines the Sales-and-Leaseback financial model to enhance profitability in ship ownership and management while mitigating liability risks. To extract valuable insights from the data and improve the analysis of market trends and operational efficiency, the utilization of Natural Language Processing (N.L.P) will be examined. Keywords: Artificial Intelligence, Machine Learning, Merchant Shipping, Oil tankers, Ship Chartering, N.L.P, Sales-and-Leaseback.